2007
DOI: 10.5897/ajb2007.000-2450
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Lagoma crude oil using pig dung

Abstract: Pig dung bacteria were isolated and screened for crude oil degrading capabilities. The pig dung was also investigated for enhancement of crude oil biodegradation. Addition of chicken manure to oil polluted soil (at 10% (v/w) pollution level) stimulated the biodegradation of lagoma crude oil used in the present study. In the soil amended with pig dung, 68.2% of the crude oil was degraded, whereas only 50.7% of same oil was degraded in the unamended soil. The pH of the amended soil rose from 6.2 to 7.2. Pig dung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 15 publications
5
29
0
1
Order By: Relevance
“…This potential is shown here to be widespread among the petroleum-utilizing bacteria isolated from cow dung and poultry manure. The petroleum-utilizing bacteria isolated from cow dung and poultry manure in the present work have previously been implicated in crude oil biodegradation, though from different sources (Obire and Akinde 2004;Okoh 2006;Yakubu 2007).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This potential is shown here to be widespread among the petroleum-utilizing bacteria isolated from cow dung and poultry manure. The petroleum-utilizing bacteria isolated from cow dung and poultry manure in the present work have previously been implicated in crude oil biodegradation, though from different sources (Obire and Akinde 2004;Okoh 2006;Yakubu 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Bacillus species and Pseudomonas species were the most predominant isolated bacterial species. Their prevalence could be attributed to their ubiquitous distribution in nature (Yakubu 2007). Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…There are no adequate literatures on the potential use of these animal manures as biostimulating agents. However, a few workers (Ijah and Antai, 2003;Okolo et al, 2005;Yakubu, 2007) have investigated the potential of these two different manures in the cleanup of soil contaminated with petroleum hydrocarbons and were found to enhance petroleum hydrocarbon biodegradation in a polluted environment. Nevertheless, their rate of biodegradation performance has not been evaluated and compared with inorganic chemical fertilizer.…”
Section: Introductionmentioning
confidence: 98%
“…The involvement of microorganisms in the degradation of petroleum hydrocarbons in the environment has been established as an economic, efficient, versatile, and environmentally friendly treatment method (Margesin and Schinner, 2001;Yakubu, 2007). One promising method that has been researched into is the application of chemical fertilizers to augment for the mineral element, particularly nitrogen and phosphorus, limitations in the soil during biodegradation (Margesin and Schinner, 1999;Ayotamuno et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Yakubu 31 found that microorganisms with oil-degrading potential are widely dispersed across nature and have been isolated in multiple ecosystems. Similar kinds of studies have been reported for microbial capability exploiting oil and its derivatives as a source of carbon and energy 32,33 .…”
Section: Discussionmentioning
confidence: 99%